2018
DOI: 10.1161/strokeaha.118.021755
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Brain Infarction by N -Acetylcysteine Derivatives

Abstract: The results indicate that detoxification of acrolein by NAC derivatives is caused through glutathione conjugation with acrolein catalyzed by glutathione -transferases, which can be stabilized by NAC derivatives. This is a new concept of acrolein detoxification by NAC derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…It is noted that NAC has been used with some success in clinical conditions and experimental models in which there are increases in brain oxidative stress (Halliwell, ), namely Alzheimer's disease (Adair et al., ; Pocernich and Butterfield, ), stroke/ischemia (Uemura et al., ), and Parkinson's disease (Monti et al., ; Rahimmi et al., ). In line with preclinical work (Quintanilla et al., ), a recent clinical study showed that NAC treatment significantly reduced alcohol intake in patients who had also consumed cannabis (Squeglia et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that NAC has been used with some success in clinical conditions and experimental models in which there are increases in brain oxidative stress (Halliwell, ), namely Alzheimer's disease (Adair et al., ; Pocernich and Butterfield, ), stroke/ischemia (Uemura et al., ), and Parkinson's disease (Monti et al., ; Rahimmi et al., ). In line with preclinical work (Quintanilla et al., ), a recent clinical study showed that NAC treatment significantly reduced alcohol intake in patients who had also consumed cannabis (Squeglia et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…NAC has classically been used in the context of acetaminophen toxicity to reduce hepatic injury (141), as well as a mucolytic agent for inflammatory pulmonary conditions (142). More recently, evidence has emerged supporting the potential use of NAC in a variety of neuropsychiatric disorders, including addiction and substance use disorders (143), neurodegenerative diseases such as spinocerebellar degeneration, Parkinson's disease, and others (144), schizophrenia (145), stroke (146), traumatic brain injury (147), obsessive-compulsive and related disorders (148), and depressive disorders (149), among other pathologies (150). NAC is a precursor to glutathione, a major antioxidant in the body, and its therapeutic properties are thought to be due its role in restoring cellular and mitochondrial redox imbalance, and reducing subsequent inflammation often seen with in neuropsychiatric conditions (150, 151).…”
Section: N-acetylcysteine (Nac)mentioning
confidence: 99%
“…The pathogenesis of cerebral infarction is mainly related to the metabolite level and vascular function in patients, and it is also affected by the expression of some genes or pathways [ 13 ]. Studies have shown that N-acetylcysteine plays an important role in the pathogenesis of cerebral infarction and can affect its prognosis [ 14 ], and substances such as acrolein are also involved in this process [ 15 ]. Therefore, studying the specific factors affecting the occurrence of cerebral infarction has importance in the prevention and treatment of disease.…”
Section: Discussionmentioning
confidence: 99%